Event-related potential data from a guess the number brain-computer interface experiment on school children - Mouček, R; Vařeka, L; Prokop, T; Štěbeták, J; Brůha, P (Scientific data, 2017)
Guess the number is a simple P300-based brain-computer interface experiment. Its aim is to ask the measured participant to pick a number between 1 and 9. Then, he or she is exposed to corresponding visual stimuli and experimenters try to guess the number thought while they are observing event-related potential waveforms on-line. 250 school-age children participated in the experiments that were carried out in elementary and secondary schools in the Czech Republic. Electroencephalographic data from three EEG channels (Fz, Cz, Pz) and stimuli markers were stored. Additional metadata about the participants were collected (gender, age, laterality, the number thought by the participant, the guess of the experimenters, and various interesting additional information). Consequently, we offer the largest publicly available odd-ball paradigm collection of datasets to neuroscientific and brain-computer interface community.
Keywords: Child; Brain-Computer Interfaces; rozhraní mozek-počítač; Electroencephalography; Female; Adolescent; ženské pohlaví; Česká republika; mužské pohlaví; Humans; lidé; Male; elektroencefalografie; dítě; mladiství; Czech Republic